PERAN PROMOSI DAN KESADARAN MEREK DALAM PENGAMBILAN KEPUTUSAN PEMBELIAN DI MARKETPLACE “ALADINMALL” - Annisa Retno Utami; Inggrid Yohana (Jurnal Riset Entrepreneurship, 2023)
The aim of this research is to analyze promotions, brand awareness and purchasing decisions at "AladinMall" and to determine the influence of promotions and brand awareness on purchasing decisions at "AladinMall" partially & simultaneously. The method used is descriptive quantitative with multiple linear regression analysis. Sample used "slovin" method and obtained 100 respondents with a sample criteria being “AladinMall” users and having made transactions at “AladinMall”. The results show that the "AladinMall" promotion to customers is interesting to see, such as a lottery or giveaway for Instagram and Tiktok users. Meanwhile, in terms of brand awareness, "AladinMall" has high users, especially in brand recognition. For purchasing decisions” also has many payment method users. Based on the research results, it was found that promotion and brand awareness can influence purchasing decisions at "AladinMall".